2012
DOI: 10.1128/aem.07961-11
|View full text |Cite
|
Sign up to set email alerts
|

Infections and Coinfections of Questing Ixodes ricinus Ticks by Emerging Zoonotic Pathogens in Western Switzerland

Abstract: ABSTRACTIn Europe,Ixodes ricinusis the vector of many pathogens of medical and veterinary relevance, among themBorrelia burgdorferisensu lato and tick-borne encephalitis virus, which have been the subject of numerous investigations. Less is known about the occurrence of emerging tick-borne pathogens like Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
80
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(90 citation statements)
references
References 59 publications
6
80
4
Order By: Relevance
“…In particular, the authors showed positive interactions between Rickettsia spp. and B. lusitaniae that could have important public health consequences, since the simultaneous transmission of multiple pathogens was shown to alter host susceptibility and immune response, and increase the severity of clinical signs [25]. On the other hand, infections by rickettsial endosymbionts may preclude secondary infections with pathogenic rickettsiae [16,26,34,59].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the authors showed positive interactions between Rickettsia spp. and B. lusitaniae that could have important public health consequences, since the simultaneous transmission of multiple pathogens was shown to alter host susceptibility and immune response, and increase the severity of clinical signs [25]. On the other hand, infections by rickettsial endosymbionts may preclude secondary infections with pathogenic rickettsiae [16,26,34,59].…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of co-infections (multiple infections with pathogens of different genera) or mixed infections (multiple infections with pathogens of the same genus), could be of medical significance because of increased severity of pathologic symptoms [1]. The prevalence of co-infections has been studied mostly within Ixodes ricinus complex [2,3,4,5], whereas potential tick vectors belonging to the other genera were much less studied.…”
Section: Introductionmentioning
confidence: 99%
“…Neoehrlichia mikurensis" was validly described as a novel intracellular pathogen in 2004 by a Japanese group investigating infections caused by members of the Anaplasmataceae in rats on the small island of Mikura, 60 km east of Tokyo, Japan (4). Since then, several groups reported the discovery of highly similar DNA sequences in potential arthropod vectors such as Ixodes ovatus, Ixodes persulcatus, and Ixodes ricinus ticks in eastern Asia (5), the Netherlands (1, 6-8), Belgium (6), Germany (9), Denmark (10), the Czech Republic (11), Slovakia (12), Russia (13), Italy (3,14,15), and recently Switzerland (16). In addition, "Ca.…”
mentioning
confidence: 99%